2012
DOI: 10.1002/anie.201200122
|View full text |Cite
|
Sign up to set email alerts
|

An Electron‐Rich Molybdenum–Molybdenum Quintuple Bond Spanned by One Lithium Atom

Abstract: Take five: A unique quintuply bonded dimolybdenum complex [Mo(2)(μ-Li){μ-HC(N-2,6-Et(2)C(6)H(3))(2)}(3)] (see picture) was synthesized and characterized. The Mo-Mo interaction includes an unexpected bridging Li(+) ion. Calculations indicate the bridging Li(+) ion does not perturb the Mo-Mo bond length (2.0612(4) Å), but results in a relatively small effective Mo-Mo bond order of 3.67.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 41 publications
1
27
0
Order By: Relevance
“…Complex 3 contains two bridging H L ligands and two terminal chlorine atoms coordinating to two molybdenum atoms (Figure ). Such a bridging fashion of the ligands has been observed in a number of metal–metal‐bonded compounds to facilitate close contact of the two metal centers, particularly in the ultra‐short quintuple‐bond Cr 2 and Mo 2 compounds , , . Each Mo atom is fourfold coordinated by two N atoms from two H L molecules, the other Mo atom, and one terminal Cl atom in a distorted tetrahedral geometry.…”
Section: Resultsmentioning
confidence: 94%
“…Complex 3 contains two bridging H L ligands and two terminal chlorine atoms coordinating to two molybdenum atoms (Figure ). Such a bridging fashion of the ligands has been observed in a number of metal–metal‐bonded compounds to facilitate close contact of the two metal centers, particularly in the ultra‐short quintuple‐bond Cr 2 and Mo 2 compounds , , . Each Mo atom is fourfold coordinated by two N atoms from two H L molecules, the other Mo atom, and one terminal Cl atom in a distorted tetrahedral geometry.…”
Section: Resultsmentioning
confidence: 94%
“…Following the discovery by the Power group of the first quintuple bond in an isolable molecule, Ar′CrCrAr′, (Ar′=C 6 H 3 ‐2,6‐(C 6 H 3 ‐2,6‐ i Pr 2 ) 2 )6 and the subsequent burgeoning of the field,7 in 2009 prominent research from the group of Tsai allowed isolation of the first molecules featuring a formal bond order of five between molybdenum atoms, namely the bis(amidinate) complexes [Mo 2 {RC( N ‐2,6‐ i Pr 2 C 6 H 3 ) 2 } 2 ] (R=H, Ph), which were obtained by reduction with potassium graphite of suitable MoMo precursors 8. Since then, other compounds with CrCr9a and MoMo9b quintuple bonds have been characterized. Reactivity studies of the quintuple MM bond have been reported too 7i.…”
Section: Introductionmentioning
confidence: 99%
“…The HOMO (MoMo δ) and HOMO−1(MoMo δ) of 1 can donate electrons to a metal center in a π and σ fashion, respectively, while the LUMO (MoMo δ*) can accept electron density from the metal center by π back‐bonding. The two recently characterized paddlewheel complexes, [Cr 2 (μ‐Me){μ‐Al(CH 3 ) 2 }(μ‐AP) 2 ]14b and [(μ‐Li)Mo 2 {μ‐HC(N‐2,6‐Et 2 C 6 H 3 ) 2 } 3 ],10d where the former have both ‐AlMe 2 and ‐Me groups spanning the CrCr quadruple bond, and the latter “‐ate” species have a lithium atom bridging a quintuple bonded Mo 2 unit, could be formally thought of as being δ complexes. However, the interactions in AlCr 2 and LiMo 2 are σ bonding only.…”
Section: Methodsmentioning
confidence: 99%